Пам’яті академіка В.П. Кухаря (1942-2017) - Vovk, Andriy I. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2022)
This special issue of Ukrainica Bioorganica Acta is dedicated to Academician V.P. Kukhar (1942-2017), a well-known scientist in the field of bioorganic, heteroatom and organoelement chemistry, an outstanding organizer of science, a founder and the first director of Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine. The scientific contri-bution of V.P. Kukhar, as well as his state and public service has been widely acknowledged. V.P. Kukhar would have turned 80 this year on January 26, and the members of the editorial team of our journal decided to organize a special issue of Ukrainica Bioorganica Acta in his honor. V.P. Kukhar was born on January 26, 1942 in Kyiv. After graduating from the Institute of Chemical Technology, which was located in Dnipro at that time, he studied at the graduate school of the Institute of Organic Chemistry in Kyiv. In 1973 he defended his doctoral dissertation, worked as a senior researcher and then as a department chair. In 1985, V.P. Kukhar became an Academician of the National Academy of Sciences of Ukraine and worked as an academician-secretary of the Department of Chemistry and Chemical Technology. During 1988-1993 he held the position of the Vice President of the National Academy of Sciences of Ukraine. At the initiative of V.P. Kukhar, the extensive research in the field of bioorganic chemistry began in Ukraine in the 1980ʹs. He formulated the main directions of the bioorganic investigations at the Institute of Bioorganic Chemistry and Petrochemistry related to the synthesis of potentially bioactive compounds and their structure-bioactivity relationship, as well as study of natural bioregulators and their synthetic structural analogues. Under his supervision, the previously unknown phosphorus derivatives with P=N and P=C bonds were synthesized for the first time, new methods of stereoselective synthesis of a wide range of previously unknown phosphorus- and fluorine-containing analogues of natural substances were developed, including amino acids and some heterocycles as potential bioactive compounds, and a number of new synthons in fine organic synthesis were proposed. V.P. Kukhar was the author of more than 600 scientific publications, including 9 monographs and many patents for inventions. In Scopus, his 255 papers have more than 5000 citations in more than 2900 documents. V.P. Kukhar was a talented scientist, and he continued to work until the last days of his life. Everyone who knew him and cooperated with him always remembers his energy and enthusiasm for science, persistence and dedication to scientific work. During his remarkable more than scientific 50-year career, he always treated people openly, with respect and attention. The present issue is composed of five reviews and four research articles by scientists working in the field of V.P. Kukhar’s interests. The first is a review of the main directions of scientific activity of Academician V.P. Kukhar in synthetic bioorganic chemistry. The other reviews cover the data based on the literature on synthesis of some fluorinated pyrrolizidine, indolizidine and quinolizidine derivatives, the chemistry of difluoro-methylene phosphonates, the heterocyclizations of β-alkoxy, β-diaminoalkyl, and related β-functionalized enones with binucleophiles, as well as development of new phosphorus-containing amino acids and peptidomimetics. The research articles present the synthesis of α-tri-fluoromethyl cyclobutane-containing building blocks, latest knowledge on calix[4]arene-based phosphinic acids as inhibitors of glutathione S-transferases, the results from the study of fluorinated NH-iminophosphonates in synthesis of biorelevant α-aminophosphonic acids derivatives, and synthesis and in vitro investigations of indole alkaloid ellipticine as multitarget active compound. We are indebted to all the authors of this Issue of Ukrainica Bioorganica Acta for scientific papers supplied for publication to remember and pay tribute to Academician V.P. Kukhar.